2013
DOI: 10.1063/1.4817280
|View full text |Cite
|
Sign up to set email alerts
|

On the fully nonlinear acoustic waves in a plasma with positrons beam impact and superthermal electrons

Abstract: Arbitrary amplitude ion-acoustic waves in an unmagnetized plasma consisting of cold positive ions, superthermal electrons, and positrons beam are reported. The basic set of fluid equations is reduced to an energy-balance like equation. The latter is numerically analyzed to examine the existence regions for solitary and shock waves. It is found that only solitary waves can propagate, however, the model cannot support shocks. The effects of superthermality and beam parameters (via, positrons concentration and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…[5,12,13] Therefore, it is worthwhile to study the nonlinear wave propagation in electronpositron-ion plasmas for understanding the dynamical behaviour of astrophysical and laboratory plasmas. [14][15][16][17][18][19][20] In the latter, the authors have shown that the nonlinear waves in the plasmas having positrons behave differently. Misra et al [5] reported that the nonlinear mode of propagation and interaction in an electron-positron plasma exhibits a remarkable feature which is quite distinctive from the linear mode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5,12,13] Therefore, it is worthwhile to study the nonlinear wave propagation in electronpositron-ion plasmas for understanding the dynamical behaviour of astrophysical and laboratory plasmas. [14][15][16][17][18][19][20] In the latter, the authors have shown that the nonlinear waves in the plasmas having positrons behave differently. Misra et al [5] reported that the nonlinear mode of propagation and interaction in an electron-positron plasma exhibits a remarkable feature which is quite distinctive from the linear mode.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in a plasma system when a source of beam is inserted, it makes the system prone to a well-known streaming instability. Recently, Shan et al [20] showed that due to the increased speed of positron beam and super-thermal electrons, the region of existence, amplitude, and width of solitons can be modified. Again, very re-cently, Shan et al [21] found that with the variation in positron beam speed and positron population, and nonlinearities of the plasma system can be predominantly changed.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6–8 ] The e‐p‐i plasmas have remained one of the most studied areas in the plasma physics community for the last couple of decades. Several studies have been devoted to non‐linear electrostatic waves in e‐p‐i plasmas, [ 9–14 ] and it has been well established that wave propagation is considerably modified by the presence of positrons in e‐i plasmas. [ 15–17 ]…”
Section: Introductionmentioning
confidence: 99%
“…Dense electron-positron pairs are demonstrated to be in the early universe, in solar atmosphere, and in inertial confinement fusion schemes using ultra-intense lasers. [1][2][3] One expects to uncover some mysteries of the universe by studying dense pair plasma state created via laser-plasma interactions in the laboratory. [4] For example, ultra-bright gamma ray burst is generally accepted as arising from synchrotron emission of relativistic shocks in pair plasmas.…”
Section: Introductionmentioning
confidence: 99%